Mucilagem da ora-pro-nóbis (Pereskia aculeata Miller): aplicação em emulsionado cárneo e avaliação das propriedades funcionais mediante diferentes condições de secagem - Lise, Carla Cristina (2021)
Pereskia aculeata Miller, popularly known as Ora-pro-nóbis (OPN), is a resistant plant, easy to adapt and produce. Its leaves have mucilaginous content characterized by high levels of protein, which favors its application as an emulsifying agent in meat derivatives. However, with regard to industrial application, the processes involved in obtaining it need to be better explored. In this sense, the present work had as objectives i) to investigate the potential of emulsification and application of the lyophilized mucilage in the elaboration of mortadella, aiming at the replacement of the chicken skin; ii) evaluate the effects of the use of ethanol and the drying process on the functional properties of OPN mucilage. For the first objective, the characterization of the mucilage regarding the amino acid profile, emulsifying capacity and stability was accomplished. Four different formulations were elaborated: Standard (with chicken skin and without mucilage), F1 (without skin and without mucilage), F2 (without skin and addition of 0.05% mucilage) and F3 (without skin and addition of 0.1% mucilage). Meat emulsion stability tests, chemical composition, color, instrumental texture, multiple comparison sensory test and acceptance index were carried out. As for the second objective, the kinematics of drying in an oven were obtained for temperatures of 30, 45 and 60°C, and the adequacy of mathematical models to the experimental data was carried out. The mucilage obtained in an oven and by lyophilization were evaluated for emulsifying capacity, emulsion stability, water and oil retention capacity, foaming capacity and stability, solubility, pH and protein content. The results revealed that the OPN mucilage had emulsifying and stabilizing potential, in addition to an excellent amino acid profile, presenting all the essentials. Increases (p≤0.05) in moisture content, reduction (p≤0.05) in lipid content and caloric value were recorded with the replacement of chicken skin by mucilage. The stability of the meat emulsion was higher (p≤0.05) in the formulation with the highest mucilage content (0.1%), as well as the instrumental texture parameters, resilience and elasticity. The contribution of mucilage addition to the instrumental texture parameters was confirmed by the multiple comparison results. The formulation with the addition of 0.05% of OPN mucilage showed stable emulsion, reduced fat content, high moisture content, high firmness, adequate color and acceptance rate of 74.7%. Page's model best represented the drying kinetics for the three temperatures. The use of ethanol to obtain the mucilage had a negative effect on the protein content and on the capacity and stability of the emulsion. As for studies related to drying, a significant effect of temperature and mode of drying was verified on the functional properties, pH and protein content of the mucilage. The lyophilized OPN mucilage showed the best results in terms of emulsifying capacity and stability, good water and oil retention capacity, as well as high foaming capacity and stability, proving high application potential.